IMPLEMENTASI KURIKULUM 2013 DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP VILLANOVA, PAPUA BARAT - Teguh Terianung D.S; Nugraha Adhi Setiawan; Winda Sundari; Ema Amalia; Natalis Michael Giovanni; Adi Wulandari (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
This research raises the topic of implementating the 2013 curriculum in improving the quality of education at Villanova Manokwari Middle School, West Papua. The aim is to find out whether the implementation of the 2013 curriculum can improve the quality of education at Villanova Manokwari Middle school. This research was conducted at Villanova Manokwari Catholic Middle School in November-December 2023 using a literature study approach with qualitative methods. This results show that Villanova Catholic Middle School has implemented the 2013 curriculum with a scientific approach. The main target is the development of student competence in the domains of attitudes, skills and knowledge. This can be seen in the teaching design created by teachers at school by adapting all teaching programs to follow the provisions of the 2013 curriculum which contain 4 competency domains, namely: Spiritual attitude competency (KI-I), social attitude competency (KI-2), knowledge competency (KI-3), and skillscompetency (KI-4). Based on the competency characteristics that are the reference for the 2013 curriculum, it is known that the implementation of the 2013 curriculum in improving the quality of education places character education within the framework of the the dynamics and dialectics of the process of individual formation. This competency development is carried out through integrated thematic education at Villanova Catholic Middle School. Keywords: Implementation, 2013 curriculum.